Antimicrobial effect of Brachystegia boehmii extracts and their green synthesised silver zero-valent derivatives on burn wound infectious bacteria. Issue 1 (31st December 2022) - Sibanda, Sipho; Shoko, Ryman; Chishaya, Kudzayi; Chimwanda, Peter; Nyoni, Stephen; Ndlovu, Joice
Abstract : Brachystegia boehmii leaf extracts are ethnopharmacological known to treat microbial infections in burn wounds. Coupling the action of the traditional plant medicine and nanotechnology gives rise to innovative strategies for healing burn wounds. This study aimed to determine the effect of B. boehmii extracts and their green synthesised nanoparticles on bacteria which infect burn wounds. The effects of water, chloroform and methanolic leaf extracts were compared with the effects of the phytosynthesised silver nanoparticles on burn wound infectious bacteria. Dried leaves were extracted using the maceration technique, followed by filtration and concentration of the filtrate using a rotavapor. Drying was achieved by using a centrivap and appropriate masses were dissolved in dimethyl sulfoxide to achieve 100 mg/ml concentrations. Silver nanoparticles were synthesised using the methanol extract of the plant leaves and characterised using a UV – VIS spectrophotometer. The disc diffusion method was used to assess the bacterial susceptibility levels with Ciprofloxacin as the positive control and DMSO and 1 mM silver nitrate as the negative controls. The green synthesised silver nanoparticles produced a yellowish colour with a peak at 420 nm wavelength. They exhibited antibacterial activity against all five bacteria; Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli, Staphylococcus aureus and Staphylococcus epidermidis comparable to those of the B. boehmii leaf solvent extracts. A zone of inhibition of 20 ± 1.00 mm was obtained on the action of B. boehmii leaf extract against P. aeruginosa . Plant synthesised nanoparticles exhibited broad spectrum antibacterial activity and hence are potential future burn wound antibacterial therapeutics.